Highly selective recovery of perfluorooctanoic acid from semiconductor wastewater via adsorption on pH-stimulated poly (dimethyl amino) ethyl methacrylate microgels - Bao, Y. (Elsevier B.V., 2022)
Perfluorooctanoic acid (PFOA) is a high-value chemical which has been widely used in the semiconductor industry. There is currently a lot of work focusing on the removal of low concentration of PFOA due to its potential toxicity, whereas the recovery of high concentration of PFOA from semiconductor wastewater via adsorption could be more valuable. This work reported a novel pH-stimulated poly (dimethyl amino) ethyl methacrylate (PDMAEMA) microgel for selective PFOA recovery. The results showed that the calculated maximum adsorption capacity for PFOA on PDMAEMA microgel is as high as 2632 mg gâ1 in the presence of 5 (v/v) isopropyl alcohol (IPA). Electrostatic interaction was considered as the main adsorption mechanism combined with hydrophobic interactions. The strong interactions made the adsorption highly selective; therefore, the components in the water matrix, including acids, metal ions, and organic solvents, would not affect the adsorption performance. Meanwhile, due to the pH responsiveness of PDMAEMA microgels, PFOA could be released easily when the solution pH was adjusted to higher values. Finally, the application mode was investigated by incorporating PDMAEMA microgels into a dense membrane, in which the separation of the microgels in a water system could be effectively achieved. Â© 2022 Elsevier B.V.